Answer:
C. 8x - 16
D.
+ 6x + 8
A. 2 (x + 3)
B. 7(2 - x)
C. -8x
D. 7x
Step-by-step explanation:
c.
To solve this problem, first, one must distribute, multiply every term inside the parenthesis by the term outside,
2(4x - 8)
=(2)(4x) + (2)(-8)
= 8x - 16
d.
To solve this problem, distribute, multiply every term inside one parenthesis by every term in the other, the combine like terms,
(x + 4)(x + 2)
= (x)(x) + (4)(x) + (2)(x) + (4)(2)
=
+ 4x + 2x + 8
=
+ 6x + 8
a.
Factor, write the given expression as the product of two expressions. Take out a common factor that both terms have,
2x + 6
= 2(x + 3)
b.
Factor this expression, take out a common factor, and rewrite the expression as the product of two other expressions,
14 - 7x
7(2 - x)
c.
Combine like terms,
2x - 10x
= -8x
d.
Combine like terms to solve this problem
3x + 4x
= 7x
Treat this as an ordinary linear equation. Try to isolate x, as some value. Also remember the basic rules of inequalities: If you're dividing, or multiplying, by a negative, you flip the inequality.
Answer:
<h2>
The answer is B. $8.82</h2>
Step-by-step explanation:
given data
mints $0.96 per pound
chocolates $4.70 per pound
lollipops $0.07 each
cost of each items based on the amount item
mints $0.96*0.75= 0.72
chocolates $4.70*1.5=7.05
lollipops $0.07*15=1.05
total cost= 0.72+7.05+1.05
total cost=$8.82
Answer+Step-by-step explanation:
![\frac{1}{5} \left( 4m+20\right) =\frac{4}{5}m + \frac{20}{5} = \frac{4}{5}m + 4](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B5%7D%20%5Cleft%28%204m%2B20%5Cright%29%20%20%3D%5Cfrac%7B4%7D%7B5%7Dm%20%2B%20%5Cfrac%7B20%7D%7B5%7D%20%3D%20%5Cfrac%7B4%7D%7B5%7Dm%20%2B%204)
![9\left( \frac{5}{4} y-\frac{1}{3} \right) =\frac{9\times5}{9} y-\frac{9}{3} = 5y - 3](https://tex.z-dn.net/?f=9%5Cleft%28%20%5Cfrac%7B5%7D%7B4%7D%20y-%5Cfrac%7B1%7D%7B3%7D%20%5Cright%29%20%20%3D%5Cfrac%7B9%5Ctimes5%7D%7B9%7D%20y-%5Cfrac%7B9%7D%7B3%7D%20%3D%205y%20-%203)